Strategi Komunikasi Pemasaran Melalui Pesan Visual Dan Verbal Pada Iklan Dana Tahun 2019 - Putri Rossiyani Rezeki; Mutiara Ramadani; Mukhsin Patriansah (Penerbit dan Percetakan, CV. Picmotiv, 2026)
This study aims to analyze the visual and verbal messages contained in DANA's 2019 advertisement as a digital marketing communication medium. The research employed a descriptive qualitative method using visual communication analysis and the AIDA (Attention, Interest, Desire, Action) model. Data were collected through observation of the DANA advertisement video uploaded on YouTube and supported by relevant literature studies. The findings indicate that visual messages are conveyed through the dominant use of blue color as brand identity, simple typography, cheerful character expressions, and depictions of daily transaction activities that represent ease of use. Meanwhile, verbal messages are communicated through narration and slogans emphasizing speed, security, and convenience in digital transactions. The combination of visual and verbal messages successfully builds DANA's image as a modern, reliable, and user-friendly digital wallet service. The study concludes that DANA's 2019 advertisement effectively communicates its message to audiences and strengthens brand identity in the digital financial technology industry